Respuesta :
Answer:
[tex] \displaystyle \large{ {f}^{ - 1} (x) = \sqrt[3]{x - 5} }[/tex]
Step-by-step explanation:
To find an inverse, we swap x to f(x)/y and f(x)/y to x.
We are given:-
[tex] \displaystyle \large{f(x) = {x}^{3} + 5}[/tex]
Swap:-
To make the equation look better and easier to simplify, we will be changing f(x) to y.
Thus:-
[tex] \displaystyle \large{y= {x}^{3} + 5} \\ \displaystyle \large{x= {y}^{3} + 5}[/tex]
Now simplify to y-isolated.
Subtract both sides by 5.
[tex] \displaystyle \large{x - 5= {y}^{3} + 5 - 5} \\ \displaystyle \large{x - 5= {y}^{3} }[/tex]
Cube root both sides.
[tex] \displaystyle \large{ \sqrt[3]{x - 5} = \sqrt[3]{ {y}^{3} } } \\ \displaystyle \large{ \sqrt[3]{x - 5} = y }[/tex]
Convert y to f(x) and add exponent of -1 between f and (x).
[tex] \displaystyle \large{ \sqrt[3]{x - 5} = {f}^{ - 1} (x) }[/tex]
To indicate that the function is an inverse.
And we're done!
Answer:
f⁻¹(x) = ∛x-5
Step-by-step explanation:
y = x³ + 5
x = y³ + 5 ... replace x with y
y³ = x-5
y = ∛x-5